TRANSFORMATIONAL LEADERSHIP IMPLEMENTATION BY MADRASAH PRINCIPALS TO ENHANCE GRADUATE QUALITY IN ISLAMIC EDUCATIONAL INSTITUTIONS - Luqman, Muhamad Luqman Nuryana; Dana Dihya’ Maulal Karim (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
In the era of globalization and modernization, Islamic educational institutions such as madrasahs face significant challenges in enhancing graduate quality to ensure their competitiveness. Transformational leadership, recognized for its ability to inspire and empower staff, has become an essential approach for creating a dynamic and progressive educational environment. This study aims to answer the question of how transformational leadership practices of madrasah principals can improve graduate quality. Using a descriptive qualitative research method, this study examines the four main components of transformational leadership, as proposed by Bernard M. Bass: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Findings from Madrasah Aliyah Al-Jawami reveal that the madrasah principal plays a crucial role in inspiring and motivating both teachers and students through exemplary behavior, empowerment, and inclusive communication. The impact of this transformational leadership is evident in the improved quality of graduates, both academically and in non-academic skills, preparing them for challenges beyond school. These findings suggest that implementing transformational leadership can be an effective strategy for enhancing educational quality in Islamic institutions. Keywords: Leadership; Transformational; Graduate Quality   Abstrak Dalam era globalisasi dan modernisasi, lembaga pendidikan Islam seperti madrasah menghadapi tantangan besar dalam meningkatkan mutu lulusan agar siap bersaing secara baik. Kepemimpinan transformasional, yang dikenal mampu menginspirasi dan memberdayakan staf, menjadi pendekatan penting untuk menciptakan lingkungan pendidikan yang dinamis dan berkembang. Penelitian ini bertujuan untuk menjawab pertanyaan bagaimana praktik kepemimpinan transformasional kepala madrasah dapat meningkatkan kualitas lulusan? Dengan metode penelitian kualitatif deskriptif, penelitian ini mengkaji empat komponen utama kepemimpinan transformasional: pengaruh ideal, motivasi inspirasional, stimulasi intelektual, dan pertimbangan individual yang dikemukakan oleh Bernard M. Bass. Hasil penelitian di Madrasah Aliyah Al-Jawami menunjukkan bahwa kepala madrasah memainkan peran penting dalam menginspirasi dan memotivasi guru serta siswa melalui keteladanan, pemberdayaan, dan komunikasi yang inklusif. Dampak kepemimpinan transformasional ini terlihat pada peningkatan mutu lulusan, baik secara akademis maupun dalam keterampilan non-akademik, yang mempersiapkan mereka menghadapi tantangan di luar sekolah. Hasil ini menunjukkan bahwa penerapan kepemimpinan transformasional dapat menjadi strategi efektif dalam meningkatkan kualitas pendidikan di lembaga pendidikan islam. Kata Kunci: Kepemimpinan; Transformasional; Mulu Lulusan;